A Mathematical Model of the Skype VoIP Congestion Control Algorithm - Luca De Cicco (IEEE Transactions on Automatic Control, 2010)
Voice over Internet Protocol (VoIP) is an Internet application of ever increasing importance. The purpose of this note is to derive a mathematical model of the Skype VoIP congestion control. The proposed model is in the form of a non linear hybrid automaton, and has been validated through extensive experiments. The dynamics of the Skype sending rate, the stability of its equilibrium points and the efficiency in bandwidth utilization while avoiding network instability are analyzed. Results show that, under network congestion, the Skype sending rate is driven by the packet loss ratio and matches the available bandwidth with a steady state finite error.